Fundamentals of construction estimating - Pratt, David J. (Delmar Cengage Learning, 2011)
FUNDAMENTALS OF CONSTRUCTION ESTIMATING 3rd edition presents estimating procedures in a clear and precise manner explaining all the procedures of estimating the cost of construction work such as quantity takeoff, pricing of the contractor's work, pricing sub-trade work, pricing site overhead and compiling bid documents. This book offers readers thorough instruction on the principles of construction estimating and the skills to become a professional estimator by using drawings for two complete projects - one residential and one commercial, thereby leading the reader through the complete estimating process which can be used in various trades on many different types of construction projects.